Whole God and whole man Deification as incarnation in Maximus the Confessor - Korb, Samuel J. (2022)
Maximus the Confessor says that the Word of God wills to be embodied always and in all things. Against many who wish to render this ‘universal incarnation’ metaphorical, I attempt a literal reading. When Maximus speaks of the Word's universal incarnation, he refers to the deification of human beings, which constitutes a single reality with the Word's incarnation. For Maximus, deification perfectly realises and completes the very logic of the Word's incarnational descent: just as God became whole man while remaining whole God, human beings will become whole God while remaining wholly human. Herein all things become enhypostasised into the Word - rendered one by grace with Christ himself, through his humanity - and so the Word becomes embodied in all things.
Keywords: Maximus the Confessor; Christology; Deification; Grace; Incarnation